Television human-puppet talk show: sensationalism, conflict and emotional concerns "case study of Abla Fahita Live" - Habib, Mary Yousry Kamel (AUC Knowledge Fountain, 2013)
This study examines the effect of sensationalism in human-puppet talk shows and the rate of adoption or rejection of viewers to the new innovation for Egyptian Television â€œAbla Fahita.â€ Two theories are used as a framework: diffusion of innovation theory (DOI) and cultivation theory. The studyâ€™s main hypotheses were H1: Youngesters adopt innovativeness earlier than others in their social system. H2: Audience who watch more show episodeâ€™s segments, the more they tend to adopt sensational contents spontaneously. H3: Abla Fahita human-puppet talk showâ€™s heavy viewers tend to watch the episodes on YouTube channel than television. The primary research linked sensationalism to television talk showsâ€™ aspects to examine whether the rate of adoption or rejection to human-puppet talk show (as new innovation to Egyptian television) is due to the sensational contents or the time spent watching human-puppet shows. This study processed with conducting quantitative survey for sample of three generations; teeangers (university students), parents (second generation), and grandparents (first generation) to measure the relative speed of adoption or rejection rate to human-puppet shows across generations. The findings support the assumption that the rate of adoption to Abla Fahita human-puppet talk show as new innovation to Egyptian television increases by the decrease of age; i.e. young third generation adopt innovation earlier than others in social system. The more sensational contents presented in the episodeâ€™s segments, the more viewers tend to adopt the innovation spontaneously. The third hypothesis was rejected as the data collected showed that heavy viewers change their viewership medium from television to YouTube depending on preference and comfort, and not for show contents nor television censorship.